Vibration for engineers - Dimarogonas, Andrew D. (Prentice Hall, 1996)
This second edition is a comprehensive book for vibration engineering. The book emphasizes design and extends the discussion of design beyond handbook solutions for component sizing to include the assumptions underlying the handbook solutions. Symbolic processing is introduced for those readers who want to extend their understanding of the fundamentals of vibration analysis. It also includes historical references so that students will understand how vibration theories developed.